The Lessons of 1920 and the Imperative of Comprehending them - Hayruni, Ashot (History and Culture, 2023)
The article covers the events of 1920 and a number of mistakes made by the military-political leadership of the first republic of Armenia, which had disastrous consequences. From the April of 1920, when Soviet Russia re-entered the region, Armenia had new opportunities, the utilization of which could provide real advancements. Unfortunately, the Armenian government failed to perceive and assess the new regional geopolitical processes caused by Russia's accession, although Russia, in turn, was deeply interested in cooperation with Armenia. The RA government's policy of refusing to cooperate with Russia and relying on the Entente allies, in particular Great Britain, greatly helped M. Kemal in implementing his plan to invade Armenia.The article also explains the situation in Kars Province during the Turkish invasion and the factors that played a significant role in the war and the shameful defeats of the Armenian army on the Kars front. The root cause of these defeats was the demoralization of the Armenian troops, which in turn was due to the corrupt activities of the higher military command in Kars, particularly generals Hovsepian and Bek-Pirumian, who, despite the reports sent to Yerevan by the governor of Kars regarding their negligence, were supported by the Defense Minister R. Ter-Minasian and thus, left unpunished, that is why there were unable to organize the resistance.
Keywords: Soviet Russia; Chicherin; Sarikamish; Legran; Kars; Kemal; Treaty of Sevres; Ohanjanian; Stalin; St. Ghorghanyan; Treaty of Alexandropol